Cross-species evaluation of fibroblast activation protein alpha as potential imaging target for soft tissue sarcoma: a comparative immunohistochemical study in humans, dogs, and cats - Beer, Patricia; Pauli, Chantal; Haberecker, Martina; Grest, Paula; Beebe, Erin; Fuchs, Daniel; Markkanen, Enni; Krudewig, Christiane; Nolff, Mirja Christine (Frontiers in Oncology, 2023)
Introduction Complete surgical tumor resection is paramount in the management of soft tissue sarcoma (STS) in humans, dogs, and cats alike. Near-infrared targeted tracers for fluorescence-guided surgery (FGS) could facilitate intraoperative visualization of the tumor and improve resection accuracy. Target identification is complicated in STS due to the rarity and heterogeneity of the disease. This study aims to validate the expression of fibroblast activation protein alpha (FAP) in selected human, canine, and feline STS subtypes to assess the value of FAP as a target for FGS and to validate companion animals as a translational model. Methods Formalin-fixed and paraffin-embedded tissue samples from 53 canine STSs (perivascular wall tumor (PWT), canine fibrosarcoma (cFS), and STS not further specified (NOS)), 24 feline fibrosarcomas, and 39 human STSs (myxofibrosarcoma, undifferentiated pleomorphic sarcoma, dermatofibrosarcoma protuberans, and malignant peripheral nerve sheath tumor) as well as six canine and seven feline healthy controls and 10 inflamed tissue samples were immunohistochemically stained for their FAP expression. FAP labeling in tumor, peritumoral, healthy skin, and inflamed tissue samples was quantified using a visually assessed semiquantitative expression score and digital image analysis. Target selection criteria (TASC) scoring was subsequently performed as previously described. Results Eighty-five percent (85%) of human (33/39), 76% of canine (40/53), and 92% of feline (22/24) STSs showed FAP positivity in over 10% of the tumor cells. A high expression was determined in 53% canine (28/53), 67% feline (16/24), and 44% human STSs (17/39). The average FAP-labeled area of canine, feline, and human STSs was 31%, 33%, and 42%, respectively (p > 0.8990). The FAP-positive tumor area was larger in STS compared to healthy and peritumoral tissue samples (p < 0.0001). TASC scores were above 18 for all feline and human STS subtypes and canine PWTs but not for canine STS NOS and cFS. Conclusion This study represents the first cross-species target evaluation of FAP for STS. Our results demonstrate that FAP expression is increased in various STS subtypes compared to non-cancerous tissues across species, thereby validating dogs and cats as suitable animal models. Based on a TASC score, FAP could be considered a target for FGS.